Board Size, Ownership Diffusion, Gender Diversity, Media Exposure, dan Pengungkapan Corporate Social Responsibility (Studi Kasus pada Perusahaan Indeks SRI-KEHATI yang terdaftar di Bursa Efek Indonesia Periode 2013-2017) - Lusia Revika Septianingsih; Muhamad Muslih (Jurnal Akuntansi, 2019)
This study aims to analyze the effect of board size, ownership diffusion, gender diversity, and media exposure to CSR disclosure. The population in this study is the SRI-KEHATI index company listed on the Indonesia Stock Exchange during 2013-2017. The total sample obtained using purposive sampling technique is as many as 50 samples, consisting of 10 companies for 5 years. The analysis technique used in this study is panel data regression analysis.The results of the study show that partially, the board size affects the disclosure of corporate social responsibility and results in a negative direction. Meanwhile, ownership diffusion, gender diversity, and media exposure have no effect on disclosure of corporate social responsibility. Keywords: Board Size, Corporate Social Responsibility Disclosure (CSRD), Gender Diversity, Media Exposure, and Ownership Diffusion.